2004
DOI: 10.1038/sj.bjc.6601600
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of MAGE promoters during gastric cancer progression

Abstract: Melanoma antigen (MAGE)-encoding genes are expressed in various tumour types via demethylation of their promoter CpG islands, which are silent in all non-neoplastic tissues except for the testis and placenta. The clinicopathological significance of demethylation of MAGE genes in gastric carcinoma is not known. We investigated the promoter methylation status of MAGE-A1 and -A3 in 10 gastric cancer cell lines and in surgical specimens from 84 gastric cancer patients by methylation-specific PCR (MSP). Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 34 publications
2
56
2
1
Order By: Relevance
“…Figure 4A also shows that this region of the MAGE-A1 gene was densely methylated in parental cells that do not normally express this gene. Previous studies showed that multiple CpGs located in the regulatory region of a gene must be substantially demethylated to make the promoter accessible for transcriptional machinery (28,(40)(41)(42)(43). We expected to see similar pattern induced by BORIS and/or 5-azadC on activation in NHDF.…”
Section: Resultsmentioning
confidence: 58%
“…Figure 4A also shows that this region of the MAGE-A1 gene was densely methylated in parental cells that do not normally express this gene. Previous studies showed that multiple CpGs located in the regulatory region of a gene must be substantially demethylated to make the promoter accessible for transcriptional machinery (28,(40)(41)(42)(43). We expected to see similar pattern induced by BORIS and/or 5-azadC on activation in NHDF.…”
Section: Resultsmentioning
confidence: 58%
“…For several germ cell and trophoblast-specific genes, it has been reported that their expression in cancer cells correlates with demethylation of CpG islands in the respective promoter regions (11,12,(22)(23)(24). Consequently, such genes are easily activated in nonexpressing cells by experimental genomic demethylation using compounds, such as 5-aza-2'-deoxycytidine.…”
Section: Resultsmentioning
confidence: 99%
“…En efecto, en varias publicaciones se ha redescubierto a la hipometilación como un mecanismo de activación de oncogenes [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] . Estas publicaciones indican que la hipometilación de genes específicos, tales como MAGE 51 , synuclein-alfa 52 , MUC2 55 , maspin 57 , CAGE 56 y family A melanoma antigen 61 ocurriría en las etapas avanzadas del cáncer. Finalmente, la sobreexpresión de reconocidos oncogenes como Myc, H-ras y ciclina D1 54,60 también ha sido asociada a la hipometilación de sus regiones promotoras.…”
Section: Hipometilación Del Adn Y Cáncer Gástricounclassified